Singing the resurrection body, community, and belief in Reformation Europe - Lambert, Erin (New cultural history of music, 2017)
'Singing the Resurrection' brings music to the foreground of Reformation studies, as author Erin Lambert explores song as a primary mode for the expression of belief among ordinary Europeans in the sixteenth century, for the embodiment of individual piety, and the creation of new communities of belief